An Analysis of Illocutionary Acts in The Inside Out 2 Animated Movie - Sianipar, Wiwin Lusiana; Pangaribuan, Rotua Elfrida; Sembiring, Rony Arahta (JALL (Journal of Applied Linguistics and Literacy), 2025)
Illocutionary acts play a crucial role in conveying meaning and expressing certain intentions in communication. This study analyzes the use of illocutionary act in the Inside Out 2 animated movie to understand how the characters use their utterances to achieve their intentions and goals. The purpose of this study is to identify the types of illocutionary acts and to analyze the dominant type of illocutionary act in the character’s utterannces in the movie. This study used descriptive qualitative method. The data were collected by transcribing the dialogues and classifying the types of illocutionary acts based on Searle’s (1979) theory, which includes representative, directive, commissive, expressive, and declarative. The findings reveal that there are 320 total data and representative is the dominant type with 133 data (41%), which indicates that each character in the movie tends to informing, describing, claiming, clarifying, or agreeing. The second most frequently used is directive with 102 data (32%), followed by expressive with 61 data (19%), then commissive with 22 data (7%) and declarative with 2 data (1%) as the lowest. This study concludes that illocutionary acts in this movie can be interpreted into five types of intentions. The writer recommends this study can be used as a reference for the learning about illocutionary acts or as a reference for the similiar study with a different perspective.